THE URGENCY OF REGISTERING SKINCARE PRODUCT PACKAGING DESIGNS TO PREVENT UNFAIR BUSINESS COMPETITION - Muna, Kholifatul; Pratama, Aditya Andela (LPPM STIH Putri Maharaja, 2024)
The viral skincare trend encourages business actors to compete to launch products with innovations in content, benefits, and attractive packaging designs including materials, shapes, colors, and logos to attract consumers' attention and differentiate their products from others. However, the reality is that practices such as product counterfeiting, brand imitation, and similar packaging often occur. This not only harms genuine business actors, but also confuses consumers and damages market reputation. The purpose of this study is to analyze and identify product packaging design registrations to prevent unfair business competition. This research uses a normative juridical method by examining regulations and related legal literature. Various approaches are used to compare regulations and analyze packaging design protections. The results of this study show the importance of registering packaging designs as industrial designs or three-dimensional brands to prevent unfair business competition and protect owners from imitation and abuse. In addition, the revision of the Industrial Design, Business Competition, and Consumer Protection Law is needed so that regulations are in line with the development of the beauty industry and provide more optimal legal protection for business actors.